"Everyone comes with their own shade of green": Negotiating the meaning of transformation in Norway's agriculture and fisheries sectors. (January 2021) - Karlsson, Marianne; Hovelsrud, Grete K.
Abstract: This paper analyses how a green transformation is conceptualized by practitioners in Norway's agriculture and fisheries sectors. Drawing upon a narrative analysis and qualitative interviews in four geographical regions, we examine how practitioners understand, negotiate and contest the green transformation. The paper identifies two main cross-sectoral narratives: 'Innovative technological solutions' and 'Local sustainable resource use'. The two distinct but interrelated narratives demonstrate an inherent tension between ensuring profitability and shifting to more environmentally sound and climate friendly modes of production. The innovative technological solutions narrative draws extensively on large-scale application of technology and market arrangements, where the state is seen as provider of incentives for a new green economy. The local sustainable resource narrative rather emphasizes small-scale niche production and making use of available resources for the benefit of the economy, environment and local communities. Both narratives contest the green transformation at higher policy level when it is framed within singular focus on climate change and GHG emission cuts and instead argue for a definition that encompass broader environmental sustainability concerns. Practitioners within the fisheries and agricultural sectors promote their activities and products as sustainable and as an important part of a green transformation. By doing so, the narratives are not transformational but rather ensure a continuation of current practices with incremental adjustments that may contribute to environmental sustainability. Highlights: Empirical study on perceptions of the green transformation in the agricultural and fisheries sectors on Norway. Two narratives identified: "Innovative technological solutions" and "Local sustainable resource use". Similarities between narratives include environmental sustainability as the goal for transformation. Differences relate to scale, level industrialization and the role of community development. The narratives promote a continuation of current activities rather than transformation.